Expanding the role of impurity spectroscopy for investigating the physics of high-Z dissipative divertors. (August 2017) - Reinke, M.L.; Meigs, A.; Delabie, E.; Mumgaard, R.; Reimold, F.; Potzel, S.; Bernert, M.; Brunner, D.; Canik, J.; Cavedon, M.; Coffey, I.; Edlund, E.; et al.
Abstract: New techniques that attempt to more fully exploit spectroscopic diagnostics in the divertor and pedestal region during highly dissipative scenarios are demonstrated using experimental results from recent low-Z seeding experiments on Alcator C-Mod, JET and ASDEX Upgrade. To exhaust power at high parallel heat flux, q ∥ > 1 GW/m 2, while minimizing erosion, reactors with solid, high-Z plasma facing components (PFCs) are expected to use extrinsic impurity seeding. Due to transport and atomic physics processes which impact impurity ionization balance, so-called 'non-coronal' effects, we do not accurately know and have yet to demonstrate the maximum q ∥ which can be mitigated in a tokamak. Radiation enhancement for nitrogen is shown to arise primarily from changes in Li- and Be-like charge states on open field lines, but also through transport-driven enhancement of H- and He-like charge states in the pedestal region. Measurements are presented from nitrogen seeded H-mode and L-mode plasmas where emission from N 1 + through N 6 + are observed. Active charge exchange spectroscopy of partially ionized low-Z impurities in the plasma edge is explored to measure N 5 + and N 6 + within the confined plasma, while passive UV and visible spectroscopy is used to measure N 1 + -N 4 + in the boundary. Examples from recent JET and Alcator C-Mod experiments which employ nitrogen seeding highlight how improving spectroscopic coverage can be used to gain empirical insight and provide more data to validate boundary simulations.